Carta ao Leitor - Reali, Aline Maria de Medeiros Rodrigues (Revista Eletrônica de Educação, 2015)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> DOI: http://dx.doi.org/10.14244/198271991457 Carta ao leitor v. 9, n.3, 2015.